Essential irrigation and the economics of strawberries in a temperate climate - Morris, Joe; Else, M. A.; El Chami, D.; Daccache, Andre; Rey, Dolores; Knox, Jerry W. (Elsevier, 2017)
Strawberries are a high value crop in the UK soft fruit sector, with the majority of production grown at field-scale and under protected (polytunnel) conditions. Despite its importance to the rural economy, there is surprisingly little published scientific evidence on the economics of irrigated strawberry production and the value of water in this horticultural sector. A survey of growers, supplemented by secondary data and industry sources, shows considerable variation in key physical and financial performance indicators, both within and between different strawberry production systems, as well as evidence of good practice. Water application depths ranged widely from 800 to over 2000 m3 ha−1 according to grower and crop variety. Irrigation costs typically range between £1.30 and £2.50 m−3 of water applied, highest where storage reservoirs and public water supplies are used. The average value of irrigation water for strawberry net of costs was about £6 m−3, much higher than for field crops such as potatoes. The importance of a reliable water supply to support irrigated strawberry production is highlighted. Climate change and growing pressures on water resources are likely to force a greater interest in irrigation economics in the soft fruit sector, especially in the face of restrictions on summer abstraction and rising competition and charges for using public water supply.
Keywords: Costs and benefits; Water use efficiency; Horticulture; Soft fruit; Water value